Capacity building and human resource development for tobacco control in Latin America Capacitación y desarrollo de recursos humanos para el control del tabaco en América Latina - Frances A Stillman (Instituto Nacional de Salud Pública, 2010)
Objective. To assess capacity and human resources in Latin America countries and compare with other countries. Material and Methods. Data were gathered through needs assessments that were conducted at the 2009 World Conference on Tobacco or Health, and the 2nd Society for Research on Nicotine and Tobacco-International American Heart Foundation, Latin America Tobacco Control Conference held in Mexico City in 2009. Results. In comparing Latin America respondents to respondents from other countries, we found that the average number of years in tobacco control was higher and the majority of respondents reported higher levels of educational attainment. Respondents reported lack of funding and other resources as their number one challenge, as well as, tobacco industry interference and lack of political will to implement tobacco control policies. Conclusions. In Latin America there are some countries that have made significant progress in building their capacity and human resources to address their tobacco epidemics, but much still needs to be done. Objetivo. Realizar un diagnóstico sobre la capacitación y los recursos humanos en América Latina y comparar con otros países. Material y métodos. Los datos se obtuvieron a través de una encuesta realizada durante la Conferencia Mundial Tabaco o Salud de 2009 y la segunda Conferencia de Control del Tabaco para América Latina de la Sociedad de Investigación sobre Nicotina y Tabaco (Society for Research on Nicotine and Tobacco) y de la Fundación Interamericana del Corazón llevada a cabo en la ciudad de México en 2009. Resultados. Al comparar las respuestas de América Latina con las de otros países, observamos que el promedio de años trabajando en control del tabaco era mayor y que la mayoría reportó un mayor nivel de estudios. Los encuestados identificaron la falta de recursos y de financiamiento como su mayor desafío así como la interferencia de la industria y la falta de voluntad política para implementar políticas de control del tabaco. Conclusiones. Algunos países de América Latina han hecho enormes avances en cuanto a la capacitación de sus recursos humanos para afrontar la epidemia del tabaco, sin embargo, todavía queda mucho por hacer.